Effects of executive attention on sentence processing in aphasia. Issue 8 (2nd August 2020) - Peristeri, Eleni; Tsimpli, Ianthi Maria; Dardiotis, Efthimios; Tsapkini, Kyrana
ABSTRACT: Background: In the recent years there has been increasing interest in the effects of attentional control on syntactic comprehension, as measured in garden path sentence resolution. Persons with aphasia (PWA) experience greater penalties in garden path sentences compared to language-unimpaired adults but the origin of this deficit remains a controversial issue. One of the possible deficits has been claimed to be disambiguation of lexical cues in the sentence. However, in languages such as English with little morphological variation this connection is hard to establish. To test this hypothesis we used garden path sentences in a morphologically rich language, Greek, where morphological cues may resolve garden path at the lexical level. We further tested whether domain-general attentional control abilities and in particular shifts in attentional control predict garden path resolution in PWA and age- and education-matched controls. Aims: This study aimed to determine whether PWA were able to integrate disambiguating morphological (Case) cues while processing garden path sentences. In addition, we tested whether domain-general attentional control and in particular attentional shift from global to local and local to global information (as defined by) correlates directly with garden path resolution in PWA and healthy controls. Methods & Procedures: Fifteen participants with non-fluent/agrammatic aphasia along with fifteen age- and education-matched language-unimpaired adults performed an online self-paced reading and grammaticality judgment task that included object/subject ambiguous sentences. Syntactic ambiguity was created by the optional transitivity of verbs, while the garden path effect was resolved by morphological Case. The individuals' executive attention skills were tested through an online non-verbal global-local attention shifting task that measured costs stemming from shifting attention from the global to the local level, and vice versa. Outcomes & Results: PWA were slower and more erroneous than controls in integrating Case cues to disambiguate garden path sentences as manifested in the self-paced reading and grammaticality judgment task. In the global local task, PWA exhibited greater global-to-local (vs. local-to-global) attention shifting costs, while controls did not exhibit dissociation. In the regression analysis, garden path resolution in PWA was significantly predicted by global-to-local attention shifting costs, while controls' garden path resolution was significantly predicted by local-to-global attention shift costs. Conclusions: The present study showed for the first time that morphological cues can shed light in sentence comprehension deficits exhibited by PWA. Furthermore, domain-general attentional control abilities were significantly associated with sentence comprehension abilities in both healthy controls and PWA.